The Effect of Group Investigation Model on Learning overhead and underarm Pass in Volleyball - Moayed, Ammar; Moayed, Ghada; Jawad, Mohammed (Journal of Physical Education, 2019)
Volleyball is one of the sports that require physical and skill abilities thus many teaching models appeared to teach these abilities like group investigation model. The research aimed at identifying the effect of group investigation model on learning underarm and overhead passing in volleyball. The researchers hypothesized statistical differences between pre and posttests in learning underarm and overhead passing in volleyball as well as differences in posttests of controlling and experimental groups in learning underarm and overhead passing in volleyball. The researcher used the experimental method on (30) second year female students of physical education and sport sciences college/ university of Baghdad. Group investigation model was applied on the experimental group while the controlling group followed the traditional program. The data was collected and treated using proper statistical operations to conclude that the experimental group was better in learning the skills understudy.